Distinct Virologic Properties of African and Epidemic Zika Virus Strains: The Role of the Envelope Protein in Viral Entry, Immune Activation, and Neuropathogenesis - Ashkan Roozitalab; Chenyu Zhang; Jiantao Zhang; Ge Li; Chengyu Yang; Wangheng Hou; Qiyi Tang; Richard Y. Zhao (Pathogens, 2025)
The 2016 Zika virus (ZIKV) epidemic has largely subsided, but a key question remains. How did ZIKV evolve to become a virulent human pathogen compared to the virus of its original discovery? What specific virologic and pathologic changes contributed to increased pathogenicity in humans? Phylogenetic studies have identified two genetically distinct ZIKV, the African and Asian lineages, which differ in their pathogenicity. Previous studies including ours suggest that the envelope (E) protein plays a key role in viral entry, immune activation, and neuropathogenesis. This study aimed to further elucidate virologic and pathogenic differences between these lineages by assessing their ability to bind and replicate in host cells, induce apoptotic cell death, trigger inflammatory responses, and influence human neural progenitor cell (hNPC)-derived neurosphere formation. We compared a historic African ZIKV strain (MR766) with an epidemic Brazilian strain (BR15) and evaluated the effects of the E protein inhibitor quercetin-3-β-O-D-glucoside (Q3G) and an E protein-neutralizing antibody (AbII). Our results revealed distinct virologic properties and that MR766 exhibited stronger inhibition of neurosphere formation due to enhanced viral binding to neuronal SH-SY5Y cells, while BR15 infection triggered a heightened pro-inflammatory cytokine response with reduced viral binding. Chimeric virus studies suggested that the E protein likely influences viral binding, replication efficiency, immune activation, and neuropathogenesis. Notably, Q3G exhibited antiviral activities against both MR766 and BR15, whereas AbII preferentially inhibited MR766. These findings highlight the virological differences between ancestral and epidemic viral strains, as well as the critical role of E protein in viral permissiveness, immune response, and neuropathogenesis, providing insights for developing targeted antiviral strategies.